Acute Schistosomal Colitis Preceded by Katayama Syndrome - Elamin Bushara, Sarra Osman; Abbas Mohammed, Sara Elfadil; Elagib, Elnour Mohamed; Yousif Mudawi, Hatim Mohamed (Journal of Digestive Endoscopy, 2017)
Schistosomiasis is prevalent in tropical and subtropical areas. It manifests as an acute or chronic illness caused by the body’s reaction to the worms’ eggs. In view of its clinical similarity to various other diseases, the disorder may cause diagnostic errors. We present a case of a Sudanese man, who presented with fever, headache, fatigue, myalgia, excessive sweating, abdominal cramps, and a high eosinophil count on blood testing. He was diagnosed with a connective tissue disorder and was started on prednisolone, but 3 weeks later, he presented with rectal bleeding. Colonoscopy showed features of moderate distal colitis. Colonic biopsies revealed several viable schistosome ova associated with aggregates of eosinophils, compatible with active colonic schistosomiasis.
Keywords: Katayama syndrome; schistosomal colitis; schistosomiasis